2005
DOI: 10.1096/fj.03-1376fje
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD44 modulates cyclooxygenase induction, VEGF generation, and cell proliferation in human vascular endothelial cells

Abstract: CD44 is a receptor for hyaluronic acid and is found on the surface of hematopoetic cells and in mesenchymal tissue. It is also expressed on endothelial cells (EC). Cyclooxygenase (COX) is the rate-limiting enzyme in the production of prostaglandins in EC. Here we show that engagement of CD44 with signaling monoclonal antibodies (mAbs) or its natural ligand hyaluronic acid induces COX-2 and prostacyclin (PGI 2 ) formation in human EC. This induction was blocked by mAbs that have been shown to inhibit CD44-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 50 publications
3
57
1
Order By: Relevance
“…These findings suggest that elevated HA levels in bronchoalveolar lavage and lung tissue in asthma or its local overproduction by tumor environment might stimulate monocyte-derived or tissue-resident macrophages to release AA and AA-derived eicosanoids through activation of cPLA 2 ␣. HA has been reported to increase PGE 2 production in human umbilical vein endothelial cells and in vivo in HA-treated mice, which was associated with simultaneous elevation of COX2 expression (76,77). Here, we showed that, even though COX2 expression was significantly increased in human monocytes and BMDM (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…These findings suggest that elevated HA levels in bronchoalveolar lavage and lung tissue in asthma or its local overproduction by tumor environment might stimulate monocyte-derived or tissue-resident macrophages to release AA and AA-derived eicosanoids through activation of cPLA 2 ␣. HA has been reported to increase PGE 2 production in human umbilical vein endothelial cells and in vivo in HA-treated mice, which was associated with simultaneous elevation of COX2 expression (76,77). Here, we showed that, even though COX2 expression was significantly increased in human monocytes and BMDM (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…16 Our finding that the angiogenic response in the Matrigel assay was decreased in the CD44-null mice, led us to re-explore the effects of acute antibody inhibition by studying the activity of another well characterized anti-CD44 antibody, IM7.8.1. 22 The specificity of this antibody was confirmed by the fact it bound to wild-type but not CD44-null ECs (data not shown). IM7.8.1 inhibited the binding of murine ECs to HA ( Figure 7A) but had no effects on cell proliferation, migration, or susceptibility to apoptotic stress (Figure 7, B-D).…”
Section: Anti-cd44 Antibody (Im781) Inhibits Tube Formation and Indmentioning
confidence: 83%
“…[15][16][17][18][19][20][21][22] Although there is evidence for the activity of RHAMM during in vivo angiogenesis, 16 the involvement of CD44 in the formation of blood vessels has not been estab-…”
mentioning
confidence: 99%
“…Addressing CD44 as a functional receptor for OPN would be important to explore the molecular mechanism underlying dysplastic changes induced by the OPN/CD44 axis. It is known that CD44 triggering stimulates diverse signalling pathways, including activation of ERK (Bourguignon et al, 2005), RAC (Teramoto et al, 2005), and RHO (Bourguignon et al, 2003), as well as secretion of soluble factors, like cytokines and metalloproteinases (Zhang et al, 2002;Bourguignon et al, 2003;Murphy et al, 2005). These pathways are potentially involved in dysplastic changes induced by OPN/CD44v6.…”
Section: Discussionmentioning
confidence: 99%